2005
DOI: 10.1017/s0265021505001298
|View full text |Cite
|
Sign up to set email alerts
|

Which is responsible for the haemodynamic response due to laryngoscopy and endotracheal intubation? Catecholamines, vasopressin or angiotensin?

Abstract: Blood pressure, heart rate, plasma epinephrine, norepinephrine and vasopressin concentrations increased slightly in response to laryngoscopy and intubation, all returning to or below baseline 5 min later with no change in angiotensin converting enzyme activity in normotensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 19 publications
4
43
2
Order By: Relevance
“…10 These responses may produce myocardial ischemia or infarction in susceptible patients. Alpha-2-Adrenergic Receptor (AR) agonists decrease the sympathetic outflows and noradrenergic activity, thereby counteracting haemodynamic fluctuations occurring at the time of intubation.…”
Section: Discussionmentioning
confidence: 99%
“…10 These responses may produce myocardial ischemia or infarction in susceptible patients. Alpha-2-Adrenergic Receptor (AR) agonists decrease the sympathetic outflows and noradrenergic activity, thereby counteracting haemodynamic fluctuations occurring at the time of intubation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although the mechanism of changes occurring in the cardiovascular system during extubation remains to be elucidated, it is associated with increased release of catecholamines as a result of the stress response. 10 In this study, we compared the hemodynamic changes and adverse events with sublingual NTG during extubation and upto twenty min thereafter .We found that after NTG, mean blood pressure were under control during and after extubation and it remained close to baseline, whereas in control group, mean arterial blood pressure were found to be persistently high during extubation, coming to baseline after ten minutes of extubation. However, increase in heart rate was comparable in both groups.…”
Section: Parametersmentioning
confidence: 88%
“…10 The drug has also been used by several authors during tracheal intubation with favorable haemodynamic effects. S. Kamra et al 11 examined the effects of 2% nitroglycerin ointment rubbed on the forehead prior to intubation and found that the rise in systolic arterial pressure was significantly lower as compared to the control group (p<0.001).…”
Section: Parametersmentioning
confidence: 99%
“…However, the shape of the stylet may hinder its removal and cause longer intubation times. In addition, a recent study showed that intubation times with video laryngoscopes can be decreased with proper preparation of the stylet and tracheal tube (7,27 Various studies indicated that laryngoscopy may cause an undesirable increase in blood pressure and heart rate in anesthetized patients (29)(30)(31)(32)(33)(34)(35). Various video laryngoscopes have been studied to elucidate the hemodynamic changes during orotracheal intubation; however, there has been no study comparing the hemodynamic response to orotracheal intubation of the McGrath Series 5 video laryngoscope and the Macintosh laryngoscope (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%